Estudio de métodos y tiempos dentro del proceso medida especial en la empresa Applus Norcontrol Sede Santa Marta (2021)
The present research work determines the procedures on how to carry out a process of a study of methods and times with the sole objective of recognizing the time necessary in the development of the activities that were the object of study in the Applus Norcontrol company in the Measurement process. Special headquarters Santa Marta. A study of methods and times consists of identifying what the current situation of the company is and through an exhaustive analysis of management indicators, work methods and identification of bottlenecks, in this way modifications were proposed and established in the execution of the activities that were objects of study, later a series of trainings was carried out on the critical phases that were found. Next, a comparison of the times before and after the established improvements was made and an average reduction in the execution time of 38.55% was observed, and then the implementation of improvement techniques in the process was sought.